2013
DOI: 10.1080/00049670.2013.832847
|View full text |Cite
|
Sign up to set email alerts
|

The changing perspectives of librarians in theBetter Beginningsfamily literacy program

Abstract: Libraries across Australia are becoming increasingly involved in the development and implementation of family literacy programs, placing librarians at the centre of this initiative. Better Beginnings is a family literacy program developed by the State Library of Western Australian and delivered throughout the state. The program involves a partnership between public libraries, health professionals and local governments that has developed to support the delivery of early literacy resources and strategies to pare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…The program was developed by the State Library of Western Australia and is based on strong cooperation between health professionals, local governments and public libraries (see Barratt-Pugh, Anderson & North, 2013). Key elements of the program over the four-year period of this study included:…”
Section: Contextmentioning
confidence: 99%
“…The program was developed by the State Library of Western Australia and is based on strong cooperation between health professionals, local governments and public libraries (see Barratt-Pugh, Anderson & North, 2013). Key elements of the program over the four-year period of this study included:…”
Section: Contextmentioning
confidence: 99%
“…These studies draw on interviews and questionnaires with parents, early years providers, health visitors and library staff. In their evaluation of Better Beginnings, for example, Barratt-Pugh et al (2013) concluded that the gift of the book prepared the way for wide-ranging discussions about language and literacy between health visitor and parent. Similarly, Coldwell et al (2012) found that book-gifting was the catalyst for long-lasting changes linked, for example, to parents' participation in literacy or mathematics classes, and access to other services, such as libraries or workshops.…”
Section: (D) Book As Storymentioning
confidence: 99%
“…Over recent years, Australian libraries have been highly proactive in developing and implementing family literacy programs. Further, libraries are increasingly partnering with family literacy programs and becoming part of the Let's Read distribution and support network (Barratt-Pugh, Anderson, & North, 2013).…”
Section: Family Literacy Bookgifting Programsmentioning
confidence: 99%
“…The research instruments were somewhat modified each year to capture the ongoing impact and sustainability of Better Beginnings, but were similar enough to allow for comparisons over time. A longitudinal study of data from the first four evaluations was made in order to examine the implementation of the program from a longitudinal perspective (Barratt-Pugh & Rohl, 2012).…”
Section: Extending the Program And Evaluation Cyclementioning
confidence: 99%
See 1 more Smart Citation